Adaptive Management of Clean Water: Strengthening Environmental Governance in Dhaka, Bangladesh - Kapoor, Preeti (Adaptive Governance Research, 2024)
Purpose: This study investigates the dynamics of adaptive control in smooth water provision in Dhaka, Bangladesh, focusing on water exceptional pleasure, governance effectiveness perceptions, and water trying out frequency. Subjects and Methods: Utilizing a blended-methods technique, inclusive of regression, correlation analyses, and ANCOVA, the studies shed light on the elaborate interplay amongst these variables. Results: Results imply a widespread improvement in water great satisfaction following an intervention geared toward enhancing governance effectiveness. Regression analysis highlights the pivotal roles of governance perceptions and water testing frequency in influencing water best pleasure. Correlation analyses unveil the interconnectedness of those variables, emphasizing the need for holistic water control strategies. Conclusions: The examine underscores the significance of adaptive governance frameworks to address complicated water control challenges and advocates for network-centric methods in Dhaka's water provision structures.